Gouvernance du microfinancement et performance des TPE : une analyse empirique du processus de formalisation au Maroc - ESSABIR, Mohamed; TANI, Wafaa; KOUKKOUS, Abdellatif (Revue du contrôle, de la comptabilité et de l’audit, 2026)
This study assesses the effectiveness of microfinance mechanisms in supporting the formalization and organizational performance of micro and small enterprises (MSEs) in Morocco, with a focus on the Souss-Massa region. Using a quantitative design and SPSS-based regression models, the analysis examines how access to microfinance products relates to formalization outcomes through key control-related dimensions, including financial traceability enabled by digital financial tools and the quality of institutional governance. Four hypotheses (H1–H4) are tested. The findings indicate significant and strong relationships between microfinance access, formalization, and performance. In addition, financial digitalization and sound governance practices (transparency, client protection, and fair pricing) appear to strengthen the overall effectiveness and sustainability of microfinance schemes. The paper discusses implications for governance and control practices within microfinance institutions and for policy mechanisms supporting enterprise formalization.